Sign language in Papua New Guinea : a primary sign language from the Upper Lagaip Valley, Enga Province - Kendon, Adam (John Benjamins Publishing Company, 2020)
"This book presents in revised form and as a single monograph three papers on a sign language from the Enga Province of Papua New Guinea. Originally published in 1980, for more than twenty years these papers remained the only report of a sign language from that part of the world. The detailed descriptive analyses that the author provided are still fresh today, and in some respects they anticipate insights into the nature of sign languages that were not further explored until much more recently. The monograph is accompanied by two essays: Sherman Wilcox comments on value and relevance of the author's work in the light of much more recent work on the linguistics of sign languages. An essay by Lauren Reed and Alan Rumsey provides an up to date survey of what is now known about sign languages in Papua New Guinea. Information about sign languages in the Solomon Island is also included"--